2007
DOI: 10.1063/1.2747192
|View full text |Cite
|
Sign up to set email alerts
|

Field emission display device structure based on double-gate driving principle for achieving high brightness using a variety of field emission nanoemitters

Abstract: In order to apply various cold cathode nanoemitters in a field emission display (FED) and to achieve high brightness, a FED device structure with double gates and corresponding driving method have been proposed. Individual pixel addressing can be achieved by applying proper sequence of positive or negative voltage to the lower gate and upper gate, respectively. The feasibility of the device has been demonstrated by using carbon nanotube and tungsten oxide nanowire cold emitters. Display of moving images has be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 64 publications
(32 citation statements)
references
References 17 publications
0
32
0
Order By: Relevance
“…[ 1 ] In case of highly ordered nanostructure arrays, it not only has an advantage of faster device turn-on time, compactness, and sustainability compared to the conventional bulky technologies, but aligned nanostructures with a high packing density can signifi cantly enhance the FE properties of materials. [101][102][103] As discussed in two previous reviews, [ 1 , 104 ] the turnon fi eld, threshold fi eld, fi eld enhancement factor, FE current density, and its stability are the key parameters of one material FE performances. These properties are strongly dependent on the work function of an emitter surface, the radius of curvature of the emitter apex, the emission area, the aspect ratio and arrangement style of the emitter, etc.…”
Section: Enhanced Field-emission Performancesmentioning
confidence: 99%
“…[ 1 ] In case of highly ordered nanostructure arrays, it not only has an advantage of faster device turn-on time, compactness, and sustainability compared to the conventional bulky technologies, but aligned nanostructures with a high packing density can signifi cantly enhance the FE properties of materials. [101][102][103] As discussed in two previous reviews, [ 1 , 104 ] the turnon fi eld, threshold fi eld, fi eld enhancement factor, FE current density, and its stability are the key parameters of one material FE performances. These properties are strongly dependent on the work function of an emitter surface, the radius of curvature of the emitter apex, the emission area, the aspect ratio and arrangement style of the emitter, etc.…”
Section: Enhanced Field-emission Performancesmentioning
confidence: 99%
“…Using self-assembled onedimensional nanomaterial cathode such as CNTs can easily achieve large area and reduce the manufacturing cost. Recently, FEDs using other one-dimensional materials cathode such as tungsten oxide and CuO nanowire have also been reported [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, various techniques for growth of nanostructures of tungsten oxides have been developed [4,[7][8][9][10][11][12][13][14][15][16][17][18], and different types of tungsten oxide nanostructure have been reported, such as W 18 O 49 nanowire [11], W 18 O 49 nanorod [12], W 18 O 49 nanotip [13], WO 3-d 3D nanowire network [4], WO 2.9 two-dimensional (2D) nanowire network [14], mixture of WO 2 and WO 2.9 nanorods [15], WO 3 nanowire [16], hollow crystalline tungsten oxide fiber [17] and tungsten oxide tree-like structure [18]. In addition, experimental results have shown that one-dimensional (1D) nanostructures of some tungsten oxides have very good field emission (FE) properties with low turn-on field and threshold field being very closed to the best values of carbon nanotube [11,13,15], and that 3D tungsten oxide nanostructures can exhibit ultrasensitive and highly selective properties in gas sensing [19].…”
Section: Introductionmentioning
confidence: 99%
“…Nanostructured materials of tungsten oxides are attractive due to their potential application in gasochromic devices [7], electrochromic device [8], field emission display device [9], and semiconductor gas sensors [10]. Thus, various techniques for growth of nanostructures of tungsten oxides have been developed [4,[7][8][9][10][11][12][13][14][15][16][17][18], and different types of tungsten oxide nanostructure have been reported, such as W 18 O 49 nanowire [11], W 18 O 49 nanorod [12], W 18 O 49 nanotip [13], WO 3-d 3D nanowire network [4], WO 2.9 two-dimensional (2D) nanowire network [14], mixture of WO 2 and WO 2.9 nanorods [15], WO 3 nanowire [16], hollow crystalline tungsten oxide fiber [17] and tungsten oxide tree-like structure [18].…”
Section: Introductionmentioning
confidence: 99%